Reproduksi maskulinitas toksik di ruang digital: Analisis kualitatif komentar Instagram - M. Subhqi Gorisha; Hermawan, Anang; Dian Dwi Anisa (Program Studi Ilmu Komunikasi UII, 2025)
Toxic masculinity speech is a negative communication expression rooted in a culture of masculinity and giving rise to social constructions of maleness. Although global studies on toxic masculinity have been immensely expanded, research emphasizing this practice on social media in Indonesia is still limited. This study analyzes expressions of toxic masculinity in Instagram user comments about Emil Mario, one of the account owners who is frequently in the spotlight and the target of toxic speech on the platform. The research corpus was compiled from 160 comments on 10 posts from January to June 2025 and analyzed using qualitative content analysis methods, employing thematic coding. The results identified five main themes: gender stereotypes, verbal aggression, physical objectification, dominance and control, and rejection of feminine behavior. The results also found the presence of prominent local pejorative terms, confirming the conclusion that expressions of toxic masculinity also reflect local cultural characteristics in the digital space.